COMPARATIVE EVALUATION OF DENTAL CARIES AMONG PATIENTS OF 6-15 YEARS AGE PRESENTING TO THE OUTPATIENT DEPARTMENT OF AYUB COLLEGE OF DENTISTRY, ABBOTTABAD - Abdur Rehman,; Ashraf, Hina; Nadia Munir,; Rabia syed,; Kiran Nayyar,; Afifa Tariq, (Journal of Ayub Medical College Abbottabad, 2024)
Background: Dental caries in the mixed dentition stage is a common problem leading to tooth decay and extractions. This study aimed to evaluate the pattern of caries among children of 6-15 years age presenting to Ayub College of Dentistry and its association with different factors such as age, dietary habits, snacking habits, and previous dental visits. Methods: It was cross-sectional research250 participants of 6-15 years presenting to Ayub College of Dentistry from November 2023 to April 2024. Dental caries was examined and DMFT index calculated with the help of questionnaires. DMFT was correlated with age, tooth brushing habits, gender, snacking habits, and previous dental visits. Data was analyzed using SPSS software version 22. Statistical correlation tests were applied to find the association between different variables such as age group, brushing habits, snacking habits and prevalence and severity of caries. Results: Dental caries was prevalent among 79.7 percent whereas the mean DMFT of sample was 5.82±4.48. There was a trend of higher DMFT scores among male population than females. A greater DMFT score of 4.2±1.8 was seen among children of 13-15 years followed by 10-12 years (3.8±1.7) and 6-9 years (2.7±1.5). Conclusion: This study highlights the high prevalence of dental caries among children and adolescents and its association with brushing habits, snacking habits, age, gender, and previous dental visits. Regular dental check-ups, proper oral hygiene practices, and a healthy diet low in sugar are key factors in preventing dental caries in elementary school students.